The Predictive Measurement Tool (PME) in the Hungarian prison service - Czenczer, Orsolya (Form@re - Open Journal per la formazione in rete, 2025)
The Hungarian Prison Service operates a risk analysis and management system for the purpose of assessing, evaluating and managing the risks of recidivism and detention of convicted persons. The most important device of the KEK system is the so-called predictive measurement tool (in Hungarian known as PME), which conducts an assessment in order to facilitate the complex process of successful reintegration of convicted persons, the essence of which is to predict the probability of occurrence of certain risks using statistical and professional tools. In Hungary, in this process, the assessment is followed by treatment, with targeted, standard programs and the use of a so-called category system. In this study we will show how this tool works and why we consider it to be particularly effective in terms of reintegration. Lo strumento di misurazione predittiva (PME) nel sistema penitenziario ungherese. Il servizio penitenziario ungherese gestisce un sistema di analisi e gestione dei rischi allo scopo di valutare, analizzare e gestire i rischi di recidiva e detenzione delle persone condannate. Il dispositivo più importante del sistema KEK è il cosiddetto strumento di misurazione predittiva (noto come PME in lingua ungherese), che effettua una valutazione al fine di facilitare il complesso processo di reinserimento delle persone condannate, la cui essenza consiste nel prevedere la probabilità che si verifichino determinati rischi utilizzando strumenti statistici e professionali. In Ungheria, in questo processo, la valutazione è seguita dal trattamento, con programmi mirati e standardizzati e l’uso di un cosiddetto sistema di categorie. Nel presente studio presenteremo il funzionamento di questo dispositivo, nonché le ragioni per cui viene considerato particolarmente efficace in termini di reintegrazione.